Fisheries: Trade by product (Edition 2017) (OECD Agriculture Statistics, 2017)
This dataset presents statistics on trade by product: imports and exports in tonnes and US dollars, for all sorts of fish, shellfish, etc. and all types of processing. Classification is according the Harmonised System (HS, i.e. harmonized commodity description and coding system of the World Customs Organization)